Analisis Pengaruh Kinerja Keuangan terhadap Profitabilitas pada Bank Umum Konvensional di Indonesia - Rizky , Shafira; Kemas M. Husni Thamrin; Muthia, Fida (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Conventional commercial banks have an important role in the Indonesian economy by being a pillar in raising and distributing funds and providing various financial services to the public, a deep understanding of the financial performance of these banks is related to their level of profitability. This study aims to analyze the effect of financial performance on profitability in conventional commercial banks in Indonesia during the period 2018-2022. The data used in this study was obtained from the Indonesia Stock Exchange (IDX) with a sample of 16 conventional commercial banks and used panel data regression analysis techniques. The results of the analysis show that Net Interest Margin (NIM) has a positive and significant influence on Return on Assets (ROA) and Operating Expenses and Operating Income (BOPO) has a negative and significant influence on ROA. However, the variables Capital Adequacy Ratio (CAR), and Loan to Deposit Ratio (LDR) did not have a significant effect on ROA in 16 conventional commercial banks in Indonesia during the study period.